1991
DOI: 10.2535/ofaj1936.68.2-3_171
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Subclavian Artery and its Branches in Japanese Adults

Abstract: Summary: We examined the entire array of branches and the state of ramification of each branch of 144 subclavian arteries (Su) in 72 Japanese adults, and obtained the following findings.(1) The incidence of Type I -A(1) was 13.2%, the highest among the entire Su ramification. This was followed by Type I -B(1) at 9.0%, then Type I -A(2) at 6.9%, indicating considerable variation in the morphology of Su ramification. (2) Ontogenetic factors were implicated because of the existence of cases in which Su traversed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…The results were Adachi (1928) 94.6% (488) 5.4% (28) 516 Aso (1932) 96.8% (61) 3.2% (2) 63 Mori (1941) 93.1% (54) 6.9% (4) 58 Takafuji and Sato (1991) 93.1% (67) 6.9% ( Adachi (1928) on the Japanese and the data of Miyashita (1935) on the Chinese (Table 4). In the present study, the distance between the origin of the right vertebral artery and the branching point in the brachiocephalic trunk was 0 -5 mm in six of 345 bodies (1.7%), 11-25 mm in 219 bodies (63.5%) and 72 mm (the longest) in one body.…”
Section: Resultsmentioning
confidence: 90%
“…The results were Adachi (1928) 94.6% (488) 5.4% (28) 516 Aso (1932) 96.8% (61) 3.2% (2) 63 Mori (1941) 93.1% (54) 6.9% (4) 58 Takafuji and Sato (1991) 93.1% (67) 6.9% ( Adachi (1928) on the Japanese and the data of Miyashita (1935) on the Chinese (Table 4). In the present study, the distance between the origin of the right vertebral artery and the branching point in the brachiocephalic trunk was 0 -5 mm in six of 345 bodies (1.7%), 11-25 mm in 219 bodies (63.5%) and 72 mm (the longest) in one body.…”
Section: Resultsmentioning
confidence: 90%
“…However, Uemura et al (2007) were able to observe the scalenus anterior, medius, posterior, and minimus muscles in the right side in their cases. They therefore concluded that the hypothesis of Takafuji and Sato (1991) was not applicable to this anatomical situation. Komatsu et al (1984) and Yuda et al (2000) suggested that the passage of the subclavian artery in front of the scalenus anterior muscle is caused by a dorsal shift of the region to which the scalenus anterior muscle is inserted.…”
Section: Discussionmentioning
confidence: 89%
“…Takafuji and Sato (1991) suggested that the mechanism of the abnormality was caused by the disappearance of the primordium of the scalenus anterior muscle and the remaining portion of the primordium of the scalenus minimus muscle, resulting in the subclavian artery passing in front of the scalenus muscle (developing scalenus minimus muscle). However, Uemura et al (2007) were able to observe the scalenus anterior, medius, posterior, and minimus muscles in the right side in their cases.…”
Section: Discussionmentioning
confidence: 98%
“…Milliez i Sakka [13] state that the ASM and the MSM develop from a common premuscle mass, which is later penetrated by the BP and the SA [13]. Takafuji and Sato [21] suggest that the original ASM has divergent fibres -anterior and posterior to the SA -with the latter fibres receding during the development of the neck. The authors hypothesize that the persistence of the posterior fibres may affect the relation of the ASM to the BP [21].…”
Section: Discussionmentioning
confidence: 99%
“…Takafuji and Sato [21] suggest that the original ASM has divergent fibres -anterior and posterior to the SA -with the latter fibres receding during the development of the neck. The authors hypothesize that the persistence of the posterior fibres may affect the relation of the ASM to the BP [21]. The interaction of the neural primordium to the premuscle mass [15] and the blood vessels [2] is considered as the key factor in the development of the anatomical variations of the neck and the axilla.…”
Section: Discussionmentioning
confidence: 99%